Magnetoresistive study of the antiferromagnetic-weak ferromagnetic transition in single-crystal La2CuO4+d - Belevtsev, B.I.; Dalakova, N.V.; Savitsky, V.N.; Bondarenko, A.V.; Panfilov, A.S.; Braude, I.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Resistive measurements were made to study the magnetic field-induced antiferromagnetic (AF)—weak ferromagnetic (WF) transition in the La2CuO4 single crystal. The magnetic field (dc or pulsed) was applied normally to the CuO2 layers. The transition manifested itself in a drastic decrease of the resistance in critical fields of 5–7 T. The study is the first to display the effect of the AF–WF transition on the conductivity of the La2CuO4 single crystal in the direction parallel to the CuO2 layers. The results provide support for the three-dimensional nature of the hopping conduction of this layered oxide.